MANAJEMEN PRODUKSI SIARAN RADIO PATRA FM DALAM MELESTARIKAN BUDAYA MINANG DI KECAMATAN MANDAU - Novika Ranti; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Radio Patra FM is one of the radio in Mandau district. Broadcasting the program with the theme of the region, minang program is one of the best programs for the regional categories that exist in Patra FM radio. Minang program has existed since Patra FM radio stands 25 years ago and until now still be the best program in Patra FM radio. Through this minang program is expected to become one of the containers to preserve minang culture. Thus this research aims to find out how the management of Patra FM radio production in preserving minang culture in Mandau district.This research uses qualitative method with descriptive approach. The object of this research is the management of Patra FM radio production in preserving minang culture in Mandau district. Subjects of this study consisted of radio owners, broadcasters, program planners and listeners, using purposive sampling method. Data collection techniques used were interview, observation and documentation. Data analysis techniques used descriptive qualitative.The results of this study indicate that Patra FM radio implement planning, organizing, actuating and controlling (POAC) in radio production management. Planning Phase (planning) includes content or topic planning, cost, programming and STP (segmentation, targeting, and positioning). The second stage Organizing (organizing). The position of the employees has been tailored to the expertise possessed and there are several employees who have multiple positions. The third stage is Actuating (movement). The presence of the operator's directions to the broadcasters during the broadcast, and for the overnight program at minang (rabab, skits, and saluang) only broadcast the sound recordings. The last stage is Controlling (supervision). Radio Patra FM for minang program will conduct joint evaluation if the number of callers is not in accordance with the target and supervision during the production process takes place. All series of processes is a form of production management process minang program in Patra FM radio in preserving minang culture in Mandau district.Keyword : management, production, radio, program, minang culture